THE WASHBACK OF ENGLISH SUMMATIVE TEST; HIGH SCHOOL TEACHER'S AND STUDENTS' PERCEPTIONS - Winarti, Muncar; Nurhasanah, Amalia (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2021)
This study aims at investigating the implementation of the English summative test for the twelfth- grade students at SMAN 4 Tebo from the students‟ and English teacher‟s perception. This paper attempts to display several impacts of English summative test to the students. This was a descriptive qualitative study where the researchers conducted an in-depth interview and distributed questionnaires to gather the data. Participants in this study were an English teacher and several twelfth-grade students. There were positive and negative washback from the analysis of teacher's perceptions and students' perceptions about summative tests. It can be concluded that the test only helps the students to pass the English summative test which was considered as a negative washback. Furthermore, the process of teaching which was oriented to achieve the four language skills stated incompetence was constituted as positive washback.